THE CONCEPT AND MEANING OF AL-AMAL WA AL-SANA IN ISLAMIC ECONOMY - Amsari, Syahrul; Anggara, Windu; zakiah, zakiah (Proceeding International Seminar of Islamic Studies, 2023)
Al-amal wa al-sana is a concept in Islamic economics that refers to the principles of work and productivity in achieving prosperity and social welfare. This concept emphasizes the importance of hard work and productive efforts in meeting the necessities of life and building a prosperous society. The meaning of al-amal wa al-sana in Islamic economics can be analyzed from the point of view of the Qur'an and Sunnah. The Qur'an teaches that humans must work hard and productively to meet their needs and build a just and prosperous society. Sunnah also provides concrete examples of the importance of hard work and productivity in achieving prosperity and well-being. In practice, the concept of al-amal wa al-sana can be implemented in various economic aspects, such as industrial development, trade, agriculture, and other sectors. In Islamic economics, this concept is also related to the principles of justice and equity in the distribution of results and the management of economic resources. However, in its application, the concept of al-amal wa al-sana also needs to pay attention to the current social, cultural and economic context as well as other existing interpretation approaches. Thus, an accurate and relevant understanding of the concept of al-amal wa al-sana in Islamic economics can be produced which can be used as a guide in developing a sustainable and just economy today. and contemporary economics and other existing interpretation approaches. Thus, an accurate and relevant understanding of the concept of al-amal wa al-sana in Islamic economics can be produced which can be used as a guide in developing a sustainable and just economy today. and contemporary economics and other existing interpretation approaches. Thus, an accurate and relevant understanding of the concept of al-amal wa al-sana in Islamic economics can be produced which can be used as a guide in developing a sustainable and just economy today